Visioner Leadership of The Head of Madrasah in Improving Teacher Professionalism - Isra Adawiyah Siregar; Mesiono Mesiono; Neliwati Neliwati (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to determine how the visionary leadership of the madrasah principal in improving teacher professionalism at MAN 2 Padang Lawas. This research seeks to explain how the visionary leadership of the madrasah principal in improving teacher professionalism at MAN 2 Padang Lawas. The method used in this research is qualitative research. Data collection techniques used observation techniques, interviews, and documentation study techniques to obtain valid data about the visionary leadership of the madrasah principal in improving teacher professionalism at MAN 2 Padang Lawas located on Jl. Sibuhuan-Old Mountain No. 96, Binanga Kec. Barumun Tengah, Padang Lawas Regency, North Sumatra. The results of the study found that the visionary leadership of the madrasah principal in improving teacher professionalism at MAN 2 Padang Lawas can be seen from the ability of the madrasah principal to realize an advanced and anticipatory madrasa by doing various ways, including preparing the madrasa vision and mission that was agreed upon by the entire community, holding activities to improve the competence and profession of teachers, conduct activities to increase the competence and talents of students' interests, conduct environmental activities for Adiwiyata madrasas, use the latest curriculum in accordance with regulations and by establishing collaborative networks with various agencies. Then it can be seen from the innovative ability of the madrasah principal to improve teacher professionalism at MAN 2 Padang Lawas by doing: first formulating new ideas in the field of teacher professionalism, second, madrasa principals carry out classroom supervision, third: creating a conducive work culture and climate, then build togetherness and kinship by inviting teachers to do positive activities usually done after the end of the semester or the end of the year.